Safety of Pelargonium extract EPs 7630 in young children with acute bronchitis - Kamin, Wolfgang; Behre, Ulrich; Helm, Klaus; Reling, Birgit; Funk, Petra; Malek, Fathi Abdul (Frontiers in Pediatrics, 2023)
Background: The efficacy and tolerability of Pelargonium sidoides DC. root extract EPs 7630 in children with acute bronchitis (AB) have been widely demonstrated. We investigated the safety and tolerability of a syrup formulation and an oral solution in pre-school children. Methods: In an open-label, randomized clinical trial (EudraCT number 2011-002652-14), children aged 1–5 years suffering from AB received EPs 7630 syrup or solution for 7 days. Safety was assessed by frequency, severity, and nature of adverse events (AE), vital signs, and laboratory values. Outcome measures for evaluating the health status were the intensity of coughing, pulmonary rales, and dyspnea, measured by the short version of the Bronchitis Severity Scale (BSS-ped), further symptoms of the respiratory infection, general health status according to the Integrative Medicine Outcomes Scale (IMOS), and satisfaction with treatment according to the Integrative Medicine Patient Satisfaction Scale (IMPSS). Results: 591 children were randomized and treated with syrup (n=403) or solution (n=188) for 7 days. In both treatment groups, the number of adverse events was similarly low and revealed no safety concerns. The most frequently observed events were infections (syrup: 7.2%; solution: 7.4%) or gastrointestinal disorders (syrup: 2.7%; solution: 3.2%). After one week’s treatment, more than 90% of the children experienced an improvement or remission of the symptoms of the BSS-ped. Further respiratory symptoms decreased similarly in both groups. At Day 7, more than 80% of the whole study population had completely recovered or showed a major improvement as assessed by the investigator and the proxy, respectively. Parents were ‘very satisfied’ or ‘satisfied’ with the treatment in 86.1% of patients in the combined syrup and solution group. Conclusion: Both pharmaceutical forms, EPs 7630 syrup and oral solution, were shown to be equally safe and well tolerated in pre-school children suffering from AB. Improvement of health status and of complaints were similar in both groups.